Reversing tozasertib resistance in glioma through inhibition of pyruvate dehydrogenase kinases. Issue 1 (23rd June 2021) - Jane, Esther P.; Premkumar, Daniel R.; Rajasundaram, Dhivyaa; Thambireddy, Swetha; Reslink, Matthew C.; Agnihotri, Sameer; Pollack, Ian F.
Abstract : Acquired resistance to conventional chemotherapeutic agents limits their effectiveness and can cause cancer treatment to fail. Because enzymes in the aurora kinase family are vital regulators of several mitotic events, we reasoned that targeting these kinases with tozasertib, a pan‐aurora kinase inhibitor, would not only cause cytokinesis defects, but also induce cell death in high‐grade pediatric and adult glioma cell lines. We found that tozasertib induced cell cycle arrest, increased mitochondrial permeability and reactive oxygen species generation, inhibited cell growth and migration, and promoted cellular senescence and pro‐apoptotic activity. However, sustained exposure to tozasertib at clinically relevant concentrations conferred resistance, which led us to examine the mechanistic basis for the emergence of drug resistance. RNA‐sequence analysis revealed a significant upregulation of the gene encoding pyruvate dehydrogenase kinase isoenzyme 4 (PDK4), a pyruvate dehydrogenase (PDH) inhibitory kinase that plays a crucial role in the control of metabolic flexibility under various physiological conditions. Upregulation of PDK1, PDK2, PDK3, or PDK4 protein levels was positively correlated with tozasertib‐induced resistance through inhibition of PDH activity. Tozasertib‐resistant cells exhibited increased mitochondrial mass as measured by 10‐ N ‐nonyl‐Acridine Orange. Inhibition of PDK with dichloroacetate resulted in increased mitochondrial permeability and cell death in tozasertib‐resistant glioma cell lines. Based on these results, we believe that PDK is a selective target for the tozasertib resistance phenotype and should be considered for further preclinical evaluations. Abstract : Acquired resistance to conventional chemotherapeutic agents limits their effectiveness and can cause cancer treatment to fail. Sustained exposure to tozasertib at clinically relevant concentrations conferred resistance in glioma. Tozasertib‐resistant cells exhibited increased mitochondrial mass and upregulation of pyruvate dehydrogenase kinases (PDK). Addition of PDK inhibitor resulted in increased mitochondrial permeability and cell death in tozasertib‐resistant glioma cell lines.